2015
DOI: 10.3892/mmr.2015.3838
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of caudal-related homeobox transcription factor 2 inhibits the growth of transplanted colorectal tumors in nude mice

Abstract: Caudal-related homeobox transcription factor 2 (CDX2) is a transcription factor, which is specifically expressed in the adult intestine. It is essential for the development and homeostasis of the intestinal epithelium and its functions as a tumor suppressor have been demonstrated in the adult colon. The present study aimed to examine the inhibitory effects of the overexpression of CDX2 on subcutaneously-transplanted tumors, derived from LoVo colon cancer cells, in nude mice, and to provide experimental evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Histopathological studies have further established that CDX2 expression is reduced in invasive colorectal cancer cells, but is restored in metastases ( 32 , 33 ). Our previous study confirmed that upregulation of CDX2 expression in human colon cancer cells inhibits invasion and migration in vitro and tumorigenicity in vivo ( 13 , 34 ). Therefore, we chose to investigate further CDX2 as a potential agent for anticancer gene therapy.…”
Section: Discussionsupporting
confidence: 80%
“…Histopathological studies have further established that CDX2 expression is reduced in invasive colorectal cancer cells, but is restored in metastases ( 32 , 33 ). Our previous study confirmed that upregulation of CDX2 expression in human colon cancer cells inhibits invasion and migration in vitro and tumorigenicity in vivo ( 13 , 34 ). Therefore, we chose to investigate further CDX2 as a potential agent for anticancer gene therapy.…”
Section: Discussionsupporting
confidence: 80%
“…In lung cancer cells, restored CDX2 expression suppressed cell proliferation by arresting the cell G1/S transition 24 . Our previous study revealed that in colon cancer cells, overexpression of CDX2 significantly inhibited cell viability and xenograft tumor formation 30,31 . However, Zhu et al reported that CDX2 promoted HCC cell proliferation by directly transactivating the oncogene CDH-17 45 .…”
Section: Discussionmentioning
confidence: 98%
“…In human CRC, a CDX2 reduction is inversely related to tumor grade, lymph node metastasis, tumor stage, and a poor prognosis 27,28 . Our previous study indicated that restoration of CDX2 expression markedly suppressed the aggressive phenotype of colon cancer cells, including viability, colony formation, and invasive and migratory abilities 2931 . Furthermore, CDX2 +/− mice were susceptible to developing colon tumor 32 .…”
Section: Introductionmentioning
confidence: 96%
“…The caudal type homeobox 2 transcription factor (CDX2) is a master regulator of intestine-specific genes crucial for the balance between intestinal cell differentiation and proliferation [ 13 , 14 ] and with a fundamental role in the maintenance of intestinal homeostasis [ 15 ]. CDX2 is highly expressed in normal colorectal epithelium, but its levels decrease in a subset of CRCs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%